Pomegranate 11 (February 2000) - (:unkn) unknown (The Pomegranate, 2000)
Readers' Forum. Few on Harran, Gender, Martyrs, Fundamentalism -- Defining Paganism / by Michael York -- Witch Wars: Factors Contributing to Conflict inCanadian Neopagan Communities / by Síân Reid -- Complex and Unpredictable Consequences: Jewish Responses to the Catastrophe of 1096 / by Fritz Muntean -- Death Under Special Circumstances: An Exploration / by Leah Samul -- Effeminate Love / John Yohalem -- Book Review: A Voice in the Forest: Conversations with Alex Sanders by 'Jimahl' / reviewed by Chas S. Clifton
The Pomegranate: A New Journal of Neopagan Thought
1 Electronic record(s) and derivatives. PDF. 30 pages. 4255178 bytes.
Keywords: Periodicals; Harran (Turkey)--History--To 1500; Neopaganism--Philosophy; Neopaganism--Relations--Neopaganism; Neopaganism--Canada; Crusades--First, 1096-1099--Jews; Crusades--First, 1096-1099--In literature; Death--Religious aspects--Neopaganism; Executed criminals--Religious aspects--Neopaganism; War casualties--Religious aspects--Neopaganism; Police--Mortality--Religious aspects--Neopaganism; Handel, George Frideric, 1685-1759. Operas; Handel, George Frideric, 1685-1759. Giulio Cesare; Effeminacy in music; Masculinity in music; DiFiosa, Jimahl, 1952- Voice in the forest--Reviews; Book reviews; Musical criticism